The reality of the professional competencies of special education coordinators and teachers working with autism spectrum disorder in the Emirate of Abu Dhabi in the light of quality requirements - Moustafa, Ashraf Mohamed; Almelah, Marwa Maher (Journal of Educational and Psychological Sciences, 2023)
The current study aimed at identify the reality of the professional competencies of special education coordinators and teachers working with autism spectrum disorder in the Emirate of Abu Dhabi in the light of quality requirements. The researcher used the descriptive analytical approach, where the main study sample consisted of (198) special education teachers and coordinators working with children with autism spectrum disorder. Pearson's correlation coefficient, Cronbach's alpha coefficient and relative importance calculation were used as statistical methods to analyze the data.The results of the research concluded that the opinions of the study sample members agree that the cognitive competencies of the coordinators and teachers of special education working with children with autism spectrum disorder are available in a medium degree, while the opinions of the coordinators and teachers of special education on the dimension of professional competencies and the necessary skills are available in a moderate degree, and the researcher recommends the need to pay attention is involved in programs for preparing special education coordinators and teachers in various tracks pre- service, with the aim of providing special education teachers with basic professional competencies in a manner that keeps pace with the development in the field of working with people with special needs, while directing great attention to special education teachers and coordinators in- service to improve their level of performance by meeting Their multiple and renewable training needs.
Keywords: Professional competencies; special education coordinators and teachers; autism spectrum disorder; quality